Blood pressure reduction combining baroreflex restoration for stroke prevention in hypertension in rats - Shu-Wei Song; Ai-Jun Liu; Chong Bai; Bei-Lin Su; Xiu-Juan Ma; Fu-Ming Shen; Jun-Li Duan; Ding-Feng Su (Frontiers Media S.A., 2010)
Blood pressure reduction is an important and effective strategy in stroke prevention in hypertensives. Recently, we found that baroreflex restoration was also crucial in stroke prevention. The present work was designed to test the hypothesis that a combination of blood pressure reduction and baroreflex restoration may be a new strategy for stroke prevention. In Experiment 1, the effects of ketanserin (0.3, 1, 3, 10 mg/kg), amlodipine (0.3, 1, 2, 3 mg/kg) and their combination (1+0.3, 1+1, 1+2, 1+3 mg/kg) on blood pressure and baroreflex sensitivity (BRS) of stroke-prone spontaneously hypertensive rats (SHR-SP) were determined under conscious state. It was found that both amlodipine and ketanserin decreased blood pressure dose-dependently. Ketanserin enfanced BRS from a very small dose but amlodipine enfanced BRS only at largest dose used. At the dose of 1 + 2 mg/kg (ketanserin + amlodipine), the combination possessed the largest synergism on blood pressure reduction. In Experiments 2 and 3, SHR-SP and two-kidney, two-clip (2K2C) renovascular hypertensive rats received life-long treatments with ketanserin (1 mg/kg) and amlodipine (2 mg/kg) or their combination (0.5+1, 1+2, 2+4 mg/kg). The survival time was recorded and the brain lesion was examined. It was found that all kinds of treatments prolonged the survival time of SHR-SP and 2K2C rats. The combination possessed a significantly better effect on stroke prevention than mono-therapies. In conclusion, combination of blood pressure reduction and baroreflex restoration may be a new strategy for the prevention of stroke in hypertension.